Citral nanoemulsion-chitosan used as wood mildew preventive, and preparation method and application thereof

High-stability small-particle-size citral nanoemulsions are prepared by compounding specific emulsifiers and mixed with chitosan, which solves the particle size and stability problems of citral nanoemulsions in wood anti-mold applications in the prior art, and achieves efficient prevention and control of wood mold.

CN119910737APending Publication Date: 2025-05-02GUANGDONG ACAD OF FORESTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510067911.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing citral nanoemulsions are not small enough in the preparation process, and are not effective in wood mildew-proof applications.

Method used

By combining castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and cosurfactant in a specific proportion, a small particle size, high-stable citral nanoemulsion with a citral content greater than 10%, was prepared, and mixed with chitosan to form a citral nanoemulsion-chitosan composite coating liquid.

Benefits of technology

It achieves high stability and small particle size of citral nanoemulsion, improves its application effect in wood mildew prevention, and can effectively prevent and control Aspergillus niger, Penicillium tangerine and Trichoderma green in wood, with a control effect of up to 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910737A_ABST
    Figure CN119910737A_ABST
Patent Text Reader

Abstract

The invention discloses a citral nanoemulsion-chitosan used as a wood mildew preventive and a preparation method and application thereof, the citral nanoemulsion-chitosan used as the wood mildew preventive is formed by mixing citral nanoemulsion and a chitosan aqueous solution; an emulsification system used by the citral nanoemulsion is a mixture of castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and a cosurfactant; the content of citral in the citral nano-emulsion is greater than or equal to 10%. According to the method, the CNE is prepared in one step through stirring, only stirring is needed, the steps of high-speed homogenization, ultrasonic treatment and the like are not needed, operation is easy and convenient, needed equipment is simple, organic solvents and oil phases are not needed, and the high-stability CNE can be obtained; the obtained CNE is semitransparent, the citral content is high and can reach 10% or above, the particle size is small, the uniformity is good, and good emulsion aging stability, heat storage stability and cold storage stability are achieved; the control efficacy of the obtained CNE-COS composite mildew preventive on trichoderma viride, penicillium citrinum and aspergillus niger reaches 100%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to citral nanoemulsion-chitosan used as a wood mildew inhibitor, a preparation method and application thereof, and belongs to the technical field of renewable resource utilization. Background Art

[0002] Wood mildew refers to the phenomenon that molds such as Trichoderma spp., Aspergillus spp., Penicillium spp., and Mucro infect wood and form mildew spots on the wood surface. Although it generally does not destroy the strength of wood, it seriously affects the appearance of wood and greatly reduces its use value. At present, the protective agents used for wood mildew prevention mainly use triazoles, organic iodides and other organic substances as active ingredients. Their mildew prevention effect is relatively high, but the production and use process has certain adverse effects on the environment and human health. Inorganic nanomaterials such as titanium oxide, silver, and silver-copper alloy have the advantages of biocidal properties, small size, large specific surface area, and unique nano-effects. In recent years, they have also been used in the prevention and control of wood mildew. However, they are prone to agglomeration and oxidation during use, which affects the mildew prevention effect.

[0003] In recent years, natural compounds derived from animals and plants have also shown potential in wood protection, such as essential oils, alkaloids, wood extracts, and chitosan. Citral, a natural broad-spectrum antibacterial agent extracted from Litsea cubeba oil, contains two isomers, neral and geranial. Citral has a pleasant lemon aroma and has a significant inhibitory effect on microorganisms such as Staphylococcus aureus, Escherichia coli, and Bacillus cereus. It is widely used in food flavoring and preservation. Its antibacterial mechanism includes destroying cell membrane integrity, regulating nucleic acid expression, inhibiting protein synthesis, and interfering with electron transfer. However, the shortcomings of citral's poor water solubility, high volatility, and easy oxidation limit its application in wood protection. Nanoemulsion is a thermodynamically stable, transparent or translucent homogeneous dispersion system with a particle size of 1 to 100 nm that is spontaneously formed by water, oil, surfactants, co-surfactants, etc. Compared with traditional emulsions, nanoemulsions have a larger specific surface area, better stability, and various special physical and chemical properties. They are often used as carriers and matrices for active substances in the fields of food, pharmaceuticals, and cosmetics.

[0004] Zou Lina used Tween-80 as a surfactant and prepared citral nanoemulsion (CNE) containing 1% citral by two steps of ultrasound and high-speed shearing. The particle size was 141.07±1.2nm and the polydispersity (PDI) was 0.226±0.02. Then CNE was mixed with chitosan (COS) solution in a certain proportion to prepare a composite coating liquid with a COS mass fraction of 1.5% and a citral mass fraction of 0% to 0.3%. It was used to preserve tangerines and can effectively inhibit the decay of fruits. Disadvantages: The preparation process of CNE requires two steps and is relatively cumbersome; it requires special high-speed dispersion equipment and is costly; CNE contains only 1% citral, which is a low content; and the particle size of CNE is relatively large.

[0005] Lu used Span 80 and Brij 97 as surfactants and ethylene glycol as co-surfactant. He first obtained a crude emulsion by homogenization and then performed ultrasound. A total of two steps were used to prepare 10% CNE with antibacterial activity. After being stored at room temperature for 7 days, the droplet size increased from 28nm to about 70nm. Disadvantages: The CNE preparation process requires two steps and is relatively cumbersome; special homogenization equipment is required, which is costly; the stability of CNE still needs to be improved.

[0006] Prakash used Tween 80 as a surfactant and prepared 5% CNE through a two-step process of homogenization and ultrasound. The droplet size was 20.44±0.52nm and the polydispersity index (PDI) was 0.44±0.03. The nanoemulsion was resistant to Listeria. After 90 days of storage at room temperature, the particle size increased to 141.28nm. Disadvantages: The CNE preparation process requires two steps and is relatively cumbersome; special homogenization equipment is required, which is costly; CNE stability still has room for improvement; the citral content in CNE is not high enough. Summary of the invention

[0007] The invention provides a citral nanoemulsion-chitosan used as a wood mildew preventer, a preparation method and use thereof, which solve the problems of insufficiently small CNE particle size, insufficiently high CNE stability and application of CNE-COS in wood mildew prevention.

[0008] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0009] A citral nanoemulsion-chitosan used as a wood mildew preventive is prepared by mixing a citral nanoemulsion and a chitosan aqueous solution; the emulsification system used in the citral nanoemulsion is a mixture of castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and a co-surfactant; wherein, in the citral nanoemulsion, the mass content of castor oil polyoxyethylene ether is 12-16%, the mass content of fatty alcohol polyoxyethylene ether is 3.9-8%, and the mass content of the co-surfactant is 1%; the co-surfactant is at least one of n-pentanol, n-hexanol or polyethylene glycol; the citral content in the citral nanoemulsion is ≥10%.

[0010] There are many kinds of existing emulsifiers, however, different target products require different emulsifiers. The inventors found in the research and development practice that different emulsifiers and the compounding ratio of emulsifiers have a great influence on the particle size, stability, solid content, etc. of citral nanoemulsion, and also affect the performance of citral nanoemulsion. The present application can prepare a small-particle, highly stable citral nanoemulsion with a citral content greater than 10% by compounding castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and co-surfactant in a specific ratio.

[0011] The existing composite emulsifier has low citral content and poor stability in the prepared citral nanoemulsion. At the same time, when preparing the existing citral nanoemulsion, oil phase, organic solvent, etc. are also required.

[0012] Unless otherwise specified, % in this application are all mass percentages.

[0013] In order to better promote the improvement of dispersibility and wood mildew resistance, preferably, the co-surfactant is at least one of n-pentanol or n-hexanol.

[0014] Different fungicides have strong selectivity for bacterial species. The present invention uses citral and chitosan, two natural resources, as raw materials to develop a green composite wood mildew inhibitor.

[0015] A method for preparing citral nanoemulsion-chitosan used as a wood mildew inhibitor comprises the following steps:

[0016] 1) Castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether, co-surfactant and citral are uniformly mixed, and water is added while stirring at a speed of 300-700 rpm. After the water is added, stirring is continued for 5 minutes to obtain CNE with a citral content of ≥10%; wherein the mass ratio of castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and co-surfactant is (12-16): (3.9-8): 1; and the co-surfactant is at least one of n-pentanol, n-hexanol or polyethylene glycol;

[0017] 2) Dissolving water-soluble chitosan (COS) in water by ultrasonication to obtain a water-soluble COS solution with a mass fraction of 1.5%; then mixing CNE, COS solution and water evenly to obtain CNE-COS used as a wood mildew inhibitor.

[0018] In the above step 1), the prepared CNE contains 12% to 16% of castor oil polyoxyethylene ether, 3.9% to 8% of fatty alcohol polyoxyethylene ether, 1% of co-surfactant, 10% to 20% of citral, and the balance is water.

[0019] In order to better ensure the anti-mildew effect of wood, in the above step 2), the CNE-COS used as the wood anti-mildew agent contains 3% to 5% citral and 0.3% to 0.7% water-soluble chitosan.

[0020] The CNE-COS used as a wood mildew inhibitor can be used for the prevention and treatment of Trichoderma.

[0021] The CNE-COS used as a wood mildew inhibitor can also be used to control Penicillium, Aspergillus and / or Mucor.

[0022] The CNE-COS used as a wood mildew inhibitor can be used for wood mildew prevention. The wood is immersed in the CNE-COS used as a wood mildew inhibitor, and the immersion time is 20 to 40 minutes under the condition of a pressure of 0.5 to 0.9 MPa, and the pressure is released, and the wood is air-dried in a cool place until the moisture content is stable (unchanged), so as to obtain CNE-COS mildew-proof wood.

[0023] The technologies not mentioned in the present invention are all referred to the prior art.

[0024] The present invention has the following beneficial effects:

[0025] 1. This technical solution prepares CNE in one step by stirring, which only requires stirring, without high-speed homogenization, ultrasound and other steps. The operation is simple and the required equipment is simple.

[0026] 2. Highly stable CNE can be obtained without organic solvents and oil phases.

[0027] 3. The obtained CNE is translucent, with a high citral content of more than 10%; the particle size is small; the particle size has a narrow single peak distribution and good uniformity.

[0028] 4. The obtained CNE has good emulsion stability over time, hot storage and cold storage.

[0029] 5. The addition of COS significantly improved the anti-mildew performance of the CNE-COS composite anti-mildew agent on wood, while reducing the loss of citral and improving its anti-loss performance.

[0030] 6. The obtained CNE-COS composite mildew inhibitor has a control efficiency of 100% against Trichoderma viride, Penicillium citrinum and Aspergillus niger. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The figure is a flow chart of the preparation of CNE-COS composite wood mildew inhibitor;

[0032] Figure 2 (a) CNE particle size distribution diagram and (b) transmission electron microscope image of CNE in Example 1;

[0033] Figure 3 (a) The retention rate of citral content in citral nanoemulsion and citral methanol solution over time in Example 1 (b) From left to right, the properties of CNE stored at high temperature (54°C) for 14 days, low temperature (0°C) for 7 days, and room temperature (25°C) for 14 days;

[0034] Figure 4 is the infrared absorption spectrum of southern pine wood before and after CNE-COS treatment in Example 1;

[0035] Figure 5 These are the untreated (left) and treated (right) southern pine specimens after 28 days of mildew resistance testing in Example 2. In the figure, (a) Aspergillus niger, (b) Penicillium citrinum, and (c) Trichoderma viride. DETAILED DESCRIPTION

[0036] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0037] Embodiment 1:

[0038] (1) Preparation of CNE

[0039] Add 4.68g of castor oil polyoxyethylene ether (El-40, Shandong Yousuo Chemical Technology Co., Ltd.), 1.17g of fatty alcohol polyoxyethylene ether (AEO-4, Shandong Yousuo Chemical Technology Co., Ltd.), 0.3g of polyethylene glycol (PEG-600, Hai'an Petrochemical Plant, Jiangsu Province), and 3.0g of citral (Jishui County Hongxing Natural Medicinal Spice Oil Factory) in a beaker, mix evenly with a magnetic stirrer, continue stirring at 700rpm and add 20.85g of water. After adding water, continue stirring at 700rpm for 5min to obtain CNE containing 10% (mass fraction) citral. The particle size is 23.10±0.08nm, the PDI is 0.135±0.009, and the particle size is a narrow unimodal distribution. Particle size distribution and transmission electron microscopy are shown in Figure 2 .

[0040] (2) CNE stability test

[0041] The stability of CNE is tested according to GB / T 1603-2001 "Method for Determination of Stability of Pesticide Emulsions", GB / T 19136-2021 "Method for Determination of Thermal Storage Stability of Pesticides" and GB / T 19137-2003 "Method for Determination of Low Temperature Stability of Pesticides".

[0042] The emulsion stability test results showed that after the nanoemulsion was diluted 200 times, the solution remained clear and transparent, without stratification or precipitation, and the emulsion stability was determined to be qualified. CNE continued to be stored at room temperature, and on the 110th day it remained clear and transparent, without stratification or precipitation, with a particle size of 28.70±0.08nm and a PDI of 0.070±0.016. The citral content was monitored by gas chromatography-mass spectrometry, such as Figure 3 As shown in (a), the citral content in CNE slowly decreased during storage, and the CNE properties remained clear and transparent on the 270th day without stratification or precipitation. It was determined that the citral retention rates on the 7th, 14th, 30th, 60th, and 270th days were 93%, 95%, 90%, 85%, and 73%, respectively. 3g of citral was dissolved in 27g of methanol (chromatographically pure, Shanghai Xingke High Purity Solvent Co., Ltd.) to prepare a 10% citral methanol solution as a control. Figure 3 As shown in (a), after being stored at room temperature for 7, 14, 30, 60 and 270 days, the citral content in the citral methanol solution decreased to 80%, 62%, 59%, 65% and 52%, respectively, indicating that the presence of citral in the form of nanoemulsion is beneficial to the retention of its effective ingredients and the long-term effect of its antifungal effect.

[0043] like Figure 3 As shown in (b), after 14 days of hot storage (54°C), CNE remained clear and transparent without stratification or precipitation. The retention rate of citral was 93%, which was slightly lower than 95% stored at room temperature (25°C), indicating good hot storage stability. The cold storage stability test results showed that CNE remained clear and transparent after 7 days at low temperature (0°C), without stratification or precipitation. The retention rate of citral was 93%, which was equivalent to 93% stored at room temperature, indicating good cold storage stability.

[0044] (3) Preparation of CNE-COS composite wood mildew inhibitor

[0045] 7.5 g of water-soluble chitosan (Shandong Luhai Lansheng Biotechnology Co., Ltd.) was weighed and dissolved in 492.5 g of water by ultrasonication to prepare a water-soluble COS solution with a mass fraction of 1.5%.

[0046] More than 500 g of 10% CNE, 466 g of 1.5% COS and 34 g of water were mixed and stirred evenly to prepare a composite wood mildew inhibitor containing 5% citral and 0.7% COS.

[0047] (4) CNE-COS pressure impregnated wood

[0048] A 50mm (grain length) × 20mm × 5mm southern pine specimen was immersed in a composite wood mildew inhibitor containing 5% citral and 0.7% COS, placed in a pressurized impregnation tank, and impregnated for 40 minutes at a pressure of 0.5MPa. After the pressure was released, the agent on the surface of the specimen was wiped dry, air-dried in a cool place until the moisture content was stable, and the specimen was ground into wood powder. The infrared spectrum of wood powder is shown in Figure 4 As shown in the figure, it can be seen that due to the stretching vibration of NH and OH in the chitosan molecule, the 3347cm -1 The infrared absorption at 2924 and 2850 cm -1 The absorption peaks are also significantly enhanced, which are attributed to the CH absorption vibration of citral and chitosan molecules. -1 The absorption peak is derived from the stretching vibration of C=O and C=C of citral, 1030cm -1 The enhancement may be due to the CO stretching vibration of the hydroxyl group of the shell sugar. -1 The absorption peaks may be caused by the C=O stretching and COC asymmetric stretching vibration of castor oil polyoxyethylene ether in CNE.In conclusion, citral and chitosan molecules can be effectively impregnated into southern pine wood.

[0049] (5) CNE-COS mildew resistance test

[0050] The mildew proof test was conducted according to GB / T 18261-2013 "Test Method for the Control of Wood Mold and Discoloration Fungi by Mildew Preventive Agents". The results showed that the control efficacy of CNE-COS compound mildew proof agent against Aspergillus niger, Penicillium citrinum and Trichoderma viride was 100%.

[0051] As a control, the composite mildew inhibitor was replaced with 5% CNE, and the southern pine wood was also treated and mildew resistance tested. The results showed that the control efficacy of 5% CNE on Aspergillus niger, Penicillium citrinum, and Trichoderma viride was 0%, indicating that the addition of COS enhanced the mildew resistance of the agent.

[0052] (6) Test on the anti-loss performance of citral in CNE-COS

[0053] When the immersion pressure was 0.9MPa, the immersion time was 40min, the citral concentration was 3%, and the chitosan concentration was set to 0% to 0.7%, the anti-loss property of CNE in the antifungal agent was tested according to GB / T 29905-2013 "Test method for loss rate of wood preservatives". The results showed that when 0.3%, 0.5%, and 0.7% chitosan were added respectively, the loss rate of citral in the antifungal agent decreased from 16.3% to 14.7%, 14.7%, and 13.3%, respectively, indicating that the addition of chitosan is conducive to the enhancement of the anti-loss property of citral.

[0054] Embodiment 2:

[0055] 3.6 g of castor oil polyoxyethylene ether (El-40, Shandong Yousuo Chemical Technology Co., Ltd.), 1.17 g of fatty alcohol polyoxyethylene ether (AEO-4, Shandong Yousuo Chemical Technology Co., Ltd.), 0.3 g of polyethylene glycol (PEG-600, Hai'an Petrochemical Plant, Jiangsu Province), and 3.0 g of citral (Jishui County Hongxing Natural Medicinal Spice Oil Factory) were added to a beaker in sequence. After mixing evenly with a magnetic stirrer, 20.7 g of water was added while stirring at 500 rpm. After the addition of water was completed, stirring was continued at 500 rpm for 5 minutes to obtain CNE containing 10% (mass fraction) citral, with a particle size of 32.26±0.20 nm and a PDI of 0.063±0.002.

[0056] 7.5 g of water-soluble chitosan (Shandong Luhai Lansheng Biotechnology Co., Ltd.) was weighed and dissolved in 492.5 g of water by ultrasonication to prepare a water-soluble COS solution with a mass fraction of 1.5%.

[0057] More than 500 g of 10% CNE, 333 g of 1.5% COS and 167 g of water were mixed and stirred evenly to prepare a composite wood mildew inhibitor containing 5% citral and 0.5% COS.

[0058] The mildew test was conducted according to GB / T 18261-2013 "Test Method for the Control of Wood Mold and Discoloration Fungi by Mildew Inhibitors". The results showed that the control effect of the CNE-COS compound mildew inhibitor on Aspergillus niger, Penicillium citrinum and Trichoderma viride was 100%. Figure 5 shown.

[0059] Embodiment 3:

[0060] In a beaker, 4.8 g of castor oil polyoxyethylene ether (El-40, Shandong Yousuo Chemical Technology Co., Ltd.), 1.17 g of fatty alcohol polyoxyethylene ether (AEO-4, Shandong Yousuo Chemical Technology Co., Ltd.), 0.3 g of n-hexanol (Shanghai McLean Biochemical Technology Co., Ltd.), and 3.0 g of citral (Jishui County Red Star Natural Medicinal Spice Oil Factory) were added in sequence. After stirring evenly at 300 rpm with a magnetic stirrer, 20.7 g of water was added while continuing to stir. After the addition of water was completed, stirring was continued at 300 rpm for 5 minutes to obtain CNE containing 10% (mass fraction) citral, with a particle size of 33.82±0.36 nm and a PDI of 0.273±0.013.

[0061] 7.5 g of water-soluble chitosan (Shandong Luhai Lansheng Biotechnology Co., Ltd.) was weighed and dissolved in 492.5 g of water by ultrasonication to prepare a water-soluble COS solution with a mass fraction of 1.5%.

[0062] More than 300g of 10% CNE, 200g of 1.5% COS and 500g of water were mixed and stirred evenly to prepare a composite wood mildew inhibitor containing 3% citral and 0.3% COS.

[0063] The anti-mold test was conducted according to GB / T 18261-2013 "Test Method for the Control of Wood Mold and Discoloration Fungi by Anti-mold Agents". The results showed that the control efficacy of the CNE-COS composite anti-mold agent against Aspergillus niger, Penicillium citrinum, and Trichoderma viride was 75%, 100%, and 100%, respectively.

[0064] As a control, the composite mildew inhibitor was replaced with 3% CNE, and the southern pine wood was also treated and mildew resistance tested. The results showed that the control efficacy of 3% CNE on Aspergillus niger, Penicillium citrinum, and Trichoderma viride was 0%, indicating that the addition of COS enhanced the mildew resistance of the agent.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that in the preparation of CNE, castor oil polyoxyethylene ether was omitted, and fatty alcohol polyoxyethylene ether was increased to 5.85 g, and the rest was referred to Example 1. A white viscous liquid was obtained, with a particle size of 256.05±4.74 nm and a PDI of 0.382±0.066.

[0067] The difference from Example 1 is that in the preparation of CNE, the amount of castor oil polyoxyethylene ether is increased to 5.265 g, and the amount of fatty alcohol polyoxyethylene ether is reduced to 0.585 g, and the rest is the same as Example 1. A translucent uniform liquid is obtained, with a particle size of 16.04±0.06 nm and a PDI of 0.030±0.000. On the 7th day, it turns white, the particle size increases to 31.90±0.32 nm, the PDI is 0.205±0.008, and the particle size uniformity deteriorates.

[0068] Comparative Example 3

[0069] The difference from Example 1 is that in the preparation of CNE, the amount of castor oil polyoxyethylene ether is reduced to 2.34 g, and the amount of fatty alcohol polyoxyethylene ether is increased to 3.51 g, and the rest is the same as Example 1. A white viscous liquid is obtained, with a particle size of 257.6±3.96 nm and a PDI of 0.218±0.088.

[0070] Comparative Example 4

[0071] The difference from Example 1 is that in the preparation of CNE, fatty alcohol polyoxyethylene ether was omitted, castor oil polyoxyethylene ether was increased to 5.85g, and the rest was referred to Example 1. A translucent uniform liquid was obtained, with a particle size of 20.50±0.00nm and a PDI of 0.183±0.032. On the 7th day, it turned white, with a particle size of 22.43±0.31nm, a PDI increased to 0.260±0.018, and a poor particle size uniformity.

[0072] Comparative Example 5

[0073] The difference from Example 1 is that in the preparation of CNE, polyethylene glycol was omitted, and the amount of fatty alcohol polyoxyethylene ether was increased to 1.47 g, and the rest was referred to Example 1. A translucent uniform liquid was obtained, with a particle size of 18.09±0.52 nm and a PDI of 0.108±0.018. Stratification occurred on the third day.

[0074] Comparative Example 6

[0075] The difference from Example 1 is that in the preparation of CNE, the amount of polyethylene glycol is increased to 0.45 g, and the amount of fatty alcohol polyoxyethylene ether is reduced to 1.02 g, and the rest is the same as Example 1. A translucent uniform liquid is obtained, with a particle size of 20.36±0.13 nm and a PDI of 0.081±0.041. After 7 days, it turns white, the particle size increases to 79.59±0.31 nm, the PDI is 0.174±0.003, and the particle size uniformity deteriorates.

[0076] Comparative Example 7

[0077] The difference from Example 1 is that in the preparation of CNE, the amount of polyethylene glycol is reduced to 0.15 g, the amount of fatty alcohol polyoxyethylene ether is increased to 1.32 g, and the rest is the same as Example 1. A translucent uniform liquid is obtained, with a particle size of 54.04±1.12 nm and a PDI of 0.227±0.014, and stratification occurs on the 4th day.

[0078] Comparative Example 8

[0079] The difference from Example 1 is that in the preparation of CNE, fatty alcohol polyoxyethylene ether is replaced by fatty alcohol polyoxyethylene polyoxypropylene block copolymer (L64, Shandong Yousuo Chemical Technology Co., Ltd.), and the rest is referred to Example 1. A milky white liquid is obtained, with a particle size of 203.65±6.72nm, a PDI of 0.208±0.016, and stratification occurs on the second day.

[0080] Comparative Example 9

[0081] The difference from Example 1 is that in the preparation of CNE, castor oil polyoxyethylene ether is replaced by polyoxyethylene ether hydrogenated castor oil (Cremophor CO 40, Hai'an Petrochemical Plant, Jiangsu Province), and the rest is referred to Example 1. A translucent uniform liquid is obtained, with a particle size of 42.15±4.69nm, a PDI of 0.177±0.030, and stratification occurs on the third day.

[0082] It can be seen from the above that the particle sizes of Comparative Examples 1, 3, and 8 are greater than 200 nm, which is much larger than 23.10 nm of Example 1 and is significantly worse than Example 1.

[0083] The average particle size of Comparative Examples 2, 4, and 6 was still less than 100 nm on the 7th day, but the appearance changed from translucent to white and the PDI increased. This was because the particle size gradually increased, the particle size distribution range became wider, and the stability was significantly worse than that of Example 1.

[0084] Comparative Examples 5, 7, 8, and 9 showed stratification within 4 days, that is, the nanoemulsion had broken, and the stability was significantly worse than that of Example 1.

Claims

1. A citral nanoemulsion-chitosan used as a wood mildew inhibitor, characterized in that: The invention is prepared by mixing citral nanoemulsion and chitosan aqueous solution; the emulsifier used in the citral nanoemulsion is a mixture of castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and a co-surfactant; wherein, in the citral nanoemulsion, the mass content of castor oil polyoxyethylene ether is 12-16%, the mass content of fatty alcohol polyoxyethylene ether is 3.9-8%, and the mass content of the co-surfactant is 1%; the co-surfactant is at least one of n-pentanol, n-hexanol or polyethylene glycol; the citral content in the citral nanoemulsion is ≥10%.

2. The citral nanoemulsion-chitosan used as a wood mildew inhibitor according to claim 1, characterized in that: The co-surfactant is at least one of n-pentanol and n-hexanol.

3. A method for preparing the citral nanoemulsion-chitosan used as a wood mildew inhibitor according to claim 1 or 2, characterized in that: The steps include: 1) Castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether, co-surfactant and citral are uniformly mixed, and water is added while stirring at a speed of 300-700 rpm. After the water is added, stirring is continued for 3-5 minutes to obtain a citral nanoemulsion with a citral content of ≥10%, referred to as CNE; wherein the mass ratio of castor oil polyoxyethylene ether, fatty alcohol polyoxyethylene ether and co-surfactant is (12-16): (3.9-8): 1; the co-surfactant is at least one of n-pentanol, n-hexanol or polyethylene glycol; 2) ultrasonically dissolving water-soluble chitosan in water to obtain a water-soluble COS solution with a mass fraction of 1.4-1.6%; then uniformly mixing the CNE and COS solutions with water to obtain citral nanoemulsion-chitosan used as a wood mildew inhibitor.

4. The preparation method according to claim 3, characterized in that: In step 1), the prepared CNE contains 12% to 16% of castor oil polyoxyethylene ether, 3.9% to 8% of fatty alcohol polyoxyethylene ether, 1% of co-surfactant, 10% of citral, and the balance is water.

5. The preparation method according to claim 3 or 4, characterized in that: In step 2), the citral nanoemulsion-chitosan used as a wood mildew inhibitor contains 3% to 5% citral and 0.3% to 0.7% water-soluble chitosan.

6. The preparation method according to claim 3 or 4, characterized in that: In step 2), the addition of chitosan to the citral nanoemulsion-chitosan used as a wood mildew inhibitor reduces the loss of citral.

7. A use of the citral nanoemulsion-chitosan as a wood mildew inhibitor according to claim 1 or 2, characterized in that: Used for the prevention and treatment of Trichoderma.

8. A use of the citral nanoemulsion-chitosan as a wood mildew inhibitor according to claim 1 or 2, characterized in that: For the control of Penicillium, Aspergillus and / or Mucor.

9. A use of the citral nanoemulsion-chitosan as a wood mildew inhibitor according to claim 1 or 2, characterized in that: Used to prevent wood mildew.

10. The use according to claim 9, characterized in that: The wood is immersed in citral nanoemulsion-chitosan used as a wood mildew inhibitor under a pressure of 0.5-0.9 MPa for 20-40 minutes, the pressure is released, and the wood is air-dried in a cool place until the moisture content is stable to obtain CNE-COS mildew-proof treated wood.